GREEN MARKETING AND CONSUMER BEHAVIOR TO PROMOTE ECO-FRIENDLY PRODUCTS - Pacora Gonzales, Santos Edinson; Cabrera Flores, Alexander Jhoel; Minchola Angulo, Mariana Carolina; Pozo Cardenas, Nicolle Brigitte; Reategui Vega, Oriana Almendra Mia; Valderrama Puscan, Marlon Walter (LACCEI, 2025)
Abstract– The study analyzes how green marketing infl uences consumer behavior in promoting eco-friendly products, especially among young people and Generation Z. It addresses the research question: What are the relationships between green marketing strategies and the pro-environmental behavior of diff erent consumers in the decision to purchase eco-friendly products? Key factors identifi ed include responsible attitudes, environmental awareness, eco-labeling, and the role of social media. Eff ective strategies such as the green marketing mix, emotional advertising, and educational campaigns are highlighted. Despite growing interest, barriers such as high prices and lack of information persist. The research proposes strengthening environmental education and adapting strategies to diff erent social profi les.